Children's tourism as a means of improving motor activity of primary school pupils in rural schools - Ruban, Vladyslav; Рубан, Владислав (Східноєвропейський національний університет ім. Лесі Українки, 2017)
The article contains data on the optimization of the motor activity of pupils of 7–10 years of rural schools by means of tourism. Positive and negative factors that influence the organization of extracurricular work in physical education with children of primary school age in the conditions of rural school are determined. Analysis of their own experimental data made it possible to determine that the volume of motor activity of a high level of rural schoolchildren is unsatisfactory, which does not allow raising the functional reserves of the organism to the proper degree. At the same time, studying the motives and needs of rural schoolchildren for physical activities, it was found that tourism is one of the most popular species. The received results became a basis for working out the program of after–hours physical culture and recreation classes «Young tourists», the content of which is presented in the article. У статті вміщено дані щодо оптимізації рухової активності учнів 7–10 років сільських шкіл засобами туризму. Визначено позитивні та негативні чинники, які впливають на організацію позакласної роботи з фізичного виховання з дітьми молодшого шкільного віку в умовах сільської школи. Аналіз власних експериментальних даних дав підставу визначити: обсяг рухової активності високого рівня сільських школярів є незадовільним, що не дає змоги належною мірою підвищувати функціональні резерви організму. Водночас, вивчаючи мотиви й потреби школярів сільської місцевості до видів занять фізичними вправами, установлено, що одним із найбільш популярних видів спорту є туризм. Отримані результати стали основою для розробки програми позаурочних фізкультурно-рекреаційних занять «Юні туристи», зміст якої представлено в статті.
Дитячий туризм як засіб підвищення рухової активності учнів початкових класів сільських шкіл.
Keywords: physical activity; children of 7–10 years; rural schools; tourism facilities; рухова активність; діти 7–10 років; сільська школа; засоби туризму